Absence of Charge Transfer State Enables Very Low V-OC Losses in SWCNT:Fullerene Solar Cells - Classen, Andrej; Einsiedler, Lukas; Heumuelier, Thomas; Graf, Arko; Brohmann, Maximilian; Berger, Felix; Kahmann, Simon; Richter, Moses; Matt, Gebhard; Forberich, Karen; Zaumseil, Jana; Brabec, Christoph (Advanced Energy Materials, 2019)
Current state-of-the-art organic solar cells (OSCs) still suffer from high losses of open-circuit voltage (V-OC). Conventional polymer:fullerene solar cells usually exhibit bandgap to V-OC losses greater than 0.8 V. Here a detailed investigation of V-OC is presented for solution-processed OSCs based on (6,5) single-walled carbon nanotube (SWCNT): [6,6]-phenyl-C-71-butyric acid methyl ester active layers. Considering the very small optical bandgap of only 1.22 eV of (6,5) SWCNTs, a high V-OC of 0.59 V leading to a low E-gap/q - V-OC = 0.63 V loss is observed. The low voltage losses are partly due to the lack of a measurable charge transfer state and partly due to the narrow absorption edge of SWCNTs. Consequently, V-OC losses attributed to a broadening of the band edge are very small, resulting in V-OC,V-SQ - V-OC,V-rad = 0.12 V. Interestingly, this loss is mainly caused by minor amounts of SWCNTs with smaller bandgaps as well as (6,5) SWCNT trions, all of which are experimentally well resolved employing Fourier transform photocurrent spectroscopy. In addition, the low losses due to band edge broadening, a very low voltage loss are also found due to nonradiative recombination, Delta V-OC,V-nonrad = 0.26 V, which is exceptional for fullerene-based OSCs.
Keywords: all-carbon absorbers; charge transfer state; organic photovoltaics; single-walled carbon nanotubes; V-OC loss analysis

Delocalisation softens polaron electronic transitions and vibrational modes in conjugated polymers - Kahmann, Simon; Loi, Maria A.; Brabec, Christoph (Journal of Materials Chemistry C, 2018)
In this work we study the photoinduced signatures of polarons in conjugated polymers and the impact of charge carrier delocalisation on their spectra. The variation of film crystallinity for two prototypical systems – blends of the homopolymer P3HT or the donor–acceptor polymer PCPDTBT with PCBM – allows probing changes of the polaron absorption in the mid infrared spectral region. Increased polaron delocalisation entails a shift of the electronic transition to lower energy in both cases. Also, infrared active vibrations soften due to a higher polymer chain order. Our findings help in providing a more complete understanding of polaron properties in conjugated materials and bring the application of the polaron absorption spectrum as an indicator for the environment on a more thoroughly studied foundatio

Exploring the Limiting Open-Circuit Voltage and the Voltage Loss Mechanism in Planar CH3NH3PbBr3 Perovskite Solar Cells - Chen, Shi; Hou, Yi; Chen, Haiwei; Richter, Moses; Guo, Fei; Kahmann, Simon; Tang, Xiaofeng; Stubhan, Tobias; Zhang, Hong; Li, Ning; Gasparini, Nicola; Ramírez Quiroz, César Omar; et al. (Advanced Energy Materials, 2016)
Perovskite solar cells based on CHNHPbBr with a band gap of 2.3 eV are attracting intense research interests due to their high open-circuit voltage (V) potential, which is specifically relevant for the use in tandem configuration or spectral splitting. Many efforts have been performed to optimize the V of CHNHPbBr solar cells; however, the limiting V (namely, radiative V:V) and the corresponding ΔV (the difference between V and V) mechanism are still unknown. Here, the average V of 1.50 V with the maximum value of 1.53 V at room temperature is achieved for a CHNHPbBr solar cell. External quantum efficiency measurements with electroluminescence spectroscopy determine the V of CHNHPbBr cells with 1.95 V and a ΔV of 0.45 V at 295 K. When the temperature declines from 295 to 200 K, the obtained V remains comparably stable in the vicinity of 1.5 V while the corresponding ΔV values show a more significant increase. Our findings suggest that the V of CHNHPbBr cells is primarily limited by the interface losses induced by the charge extraction layer rather than by bulk dominated recombination losses. These findings are important for developing strategies how to further enhance the V of CHNHPbBr-based solar cells.
Keywords: CH3NH3PbBr3 solar cells; interface materials based losses; nonradiative recombination losses; open-circuit voltage

Extending the environmental lifetime of unpackaged perovskite solar cells through interfacial design - Chen, Haiwei; Hou, Yi; Halbig, Christian Eberhard; Chen, Shi; Zhang, Hong; Li, Ning; Guo, Fei; Tang, Xiaofeng; Gasparini, Nicola; Levchuk, Ievgen; Kahmann, Simon; Ramírez Quiroz, César Omar; et al. (Journal of Materials Chemistry A, 2016)
Solution-processed oxo-functionalized graphene (oxo-G) is employed to substitute hydrophilic PEDOT:PSS as an anode interfacial layer for perovskite solar cells. The resulting devices exhibit a reasonably high power conversion efficiency (PCE) of 15.2% in the planar inverted architecture with oxo-G as a hole transporting material (HTM), and most importantly, deploy the full open-circuit voltage (V) of up to 1.1 V. Moreover, oxo-G effectively slows down the ingress of water vapor into the device stack resulting in significantly enhanced environmental stability of unpackaged cells under illumination with 80% of the initial PCE being reached after 500 h. Without encapsulation, ∼60% of the initial PCE is retained after ∼1000 h of light soaking under 0.5 sun and ambient conditions maintaining the temperature beneath 30 °C. Moreover, the unsealed perovskite device retains 92% of its initial PCE after about 1900 h under ambient conditions and in the dark. Our results underpin that controlling water diffusion into perovskite cells through advanced interface engineering is a crucial step towards prolonged environmental stability.
Keywords: Engineering controlled terms: Cell engineering; Conducting polymers; Open circuit voltage; Perovskite; Slow light; Solar cells Environmental stability; Functionalized graphene; High power conversion; Hole-transporting materials; Interface engineering; Interfacial design; Inverted architectures; Solution-processed Engineering main heading: Perovskite solar cells

Favorable Mixing Thermodynamics in Ternary Polymer Blends for Realizing High Efficiency Plastic Solar Cells - Gasparini, Nicola; Kahmann, Simon; Salvador, Michael Filipe; Perea, Jose Dario; Sperlich, Andreas; Baumann, Andreas; Li, Ning; Rechberger, Stefanie; Spiecker, Erdmann; Dyakonov, Vladimir; Portale, Giuseppe; Loi, Maria A.; et al. (Advanced Energy Materials, 2019)
Ternary blends with broad spectral absorption have the potential to increase charge generation in organic solar cells but feature additional complexity due to limited intermixing and electronic mismatch. Here, a model system comprising the polymers poly[5,5-bis(2-butyloctyl)-(2,2-bithiophene)-4,4-dicarboxylate-alt-5,5-2,2-bithiophene] (PDCBT) and PTB7-Th and PC70BM as an electron accepting unit is presented. The power conversion efficiency (PCE) of the ternary system clearly surpasses the performance of either of the binary systems. The photophysics is governed by a fast energy transfer process from PDCBT to PTB7-Th, followed by electron transfer at the PTB7-Th:fullerene interface. The morphological motif in the ternary blend is characterized by polymer fibers. Based on a combination of photophysical analysis, GIWAXS measurements and calculation of the intermolecular parameter, the latter indicating a very favorable molecular affinity between PDCBT and PTB7-Th, it is proposed that an efficient charge generation mechanism is possible because PTB7-Th predominantly orients around PDCBT filaments, allowing energy to be effectively relayed from PDCBT to PTB7-Th. Fullerene can be replaced by a nonfullerene acceptor without sacrifices in charge generation, achieving a PCE above 11%. These results support the idea that thermodynamic mixing and energetics of the polymer–polymer interface are critical design parameter for realizing highly efficient ternary solar cells with variable electron acceptors</stron
Keywords: FRET; high efficiency; ternary organic solar cells; mixing thermodynamics; photophysics

Photoinduced degradation of methylammonium lead triiodide perovskite semiconductors - Tang, Xiaofeng; Brandl, Marco; May, Benjamin; Levchuk, Ievgen; Hou, Yi; Richter, Moses; Chen, Haiwei; Chen, Shi; Kahmann, Simon; Osvet, Andres; Maier, Florian; Steinrück, Hans-Peter; et al. (Journal of Materials Chemistry A, 2016)
Photoinduced degradation is a critical obstacle for the real application of novel semiconductors for photovoltaic applications. In this paper, the photoinduced degradation of CHNHPbI in a vacuum and air (relative humidity 40%) is analyzed by ex situ and advanced in situ technologies. Without light illumination, CHNHPbI films slowly degrade under vacuum and air within 24 hours. However, we find that CHNHPbI converts to metallic lead (Pb) when exposed to vacuum and light illumination. Further, a series of lead salts (e.g. PbO, Pb(OH) and PbCO) are formed when CHNHPbI is degraded under environmental conditions, i.e. under the combination of light, oxygen and moisture. Photoinduced degradation is found to be determined by the environmental atmosphere as CHNHPbI films remain very stable under nitrogen conditions. The results from vacuum conditions underpin that the high volatility of the organic component (CHNHI) is in conflict with reaching excellent intrinsic stability due to its role in creating ion vacancies. The degradation in air suggests that both oxygen and water contribute to the fast photodecomposition of CHNHPbI into lead salts rather than water alone. Given these basic yet fundamental understandings, the design of hydrophobic capping layers becomes one prerequisite towards long-term stable perovskite-based devices.
Keywords: Engineering controlled terms: Lead; Perovskite; Salts; Slow light Environmental conditions; Intrinsic stability; Light illumination; Organic components; Photo-decomposition; Photoinduced degradation; Photovoltaic applications; Real applications Engineering main heading: Photodegradation

Polarons in Narrow Band Gap Polymers Probed over the Entire Infrared Range: A Joint Experimental and Theoretical Investigation - Kahmann, Simon; Fazzi, Daniele; Matt, Gebhard; Thiel, Walter; Loi, Maria A.; Brabec, Christoph (Journal of Physical Chemistry Letters, 2016)
We investigate the photoinduced absorption (PIA) spectra of the prototypical donor-acceptor polymer [2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT) and its silicon bridged variant Si-PCPDTBT over a spectral range from 0.07 to 1.5 eV. Comparison between time-dependent density functional theory simulations of the electronic and vibrational transitions of singlet excitons, triplet excitons, polarons, and bipolarons with the experimental results proves that the observed features are due to positive polarons delocalized on the polymer chains. We find that the more crystalline Si-bridged variant gives rise to a red-shift in the transition energies, especially in the mid-infrared (MIR) spectral range and furthermore observe that the pristine polymers' responses depend on the excitation energy. Blending with PCBM, on the other hand, leads to excitation-independent PIA spectra. By computing the response properties of molecular aggregates, we show that polarons are delocalized in not only the intra- but also the interchain direction, leading to intermolecular transitions which correspond well to experimental absorption features at the lowest energies.
Keywords: Engineering controlled terms: Blending; Computation theory; Density functional theory; Energy gap; Excitons; Polarons 2; 1; 3-Benzothiadiazole; Donor-acceptor polymers; Interchain direction; Narrow band gap polymers; Photoinduced absorption; Theoretical investigations; Time dependent density functional theory; Vibrational transitions Engineering main heading: Polymers